Safety and feasibility of therapeutic platelet depletion with Spectra Optia in a pregnant woman. Issue 4 (August 2017) - Małachowski, Roman; Grzybowska-Izydorczyk, Olga; Besson, Nelly; Szmigielska-Kapłon, Anna; Nowicki, Mateusz; Wierzbowska, Agnieszka
Abstract: Introduction: Thrombocytapheresis is an alternative treatment beneficial in rare circumstances, when cytoreductive agents are contraindicated, drug therapy gave no response or the expected response would be too slow. Here we present a case of a pregnant woman who underwent 5 thrombocytaphereses using Spectra Optia device to reduce circulating platelets (PLT) count and prepare for Cesarian section. Patient characteristics and performed treatment: A 39-year-old woman with diagnosed chronic myeloid leukemia (CML) was treated with interferon because of too high PLT count. The treatment was well tolerated but the effect was not satisfactory (PLT count remained high). Because of high risk of bleeding during childbirth, the healthcare providers decided to perform thrombocytapheresis to reduce circulating PLT count below 1000 × 10E3/μl, and to prepare the patient for a planned Cesarean section. The results are presented as mean ± SD. Results: Five therapeutic aphereses procedures were performed, with a Spectra Optia device (TerumoBCT). A mean of 1.3 ± 0.3 total blood volume was processed and we observed a mean PLT drop of 42.3 ± 17.7%. Each apheresis procedure resulted in a PLT level ≤1000 × 10E3/μl. PLT CE1 was high 50.6 ± 2.6% and reproducible. The white blood cell (WBC) loss was low (18.5% ± 11.0%). No adverse effects were observed. Conclusion: Therapeutic platelet depletion using the Spectra Optia™ Apheresis System can be effective and safe during pregnancy. Thrombocytapheresis procedures were reproducible and Spectra Optia system successfully adjusted settings to each procedure conditions. Thrombocytapheresis seems to be a viable and safe option even in pregnant women.